The Correlation Between Spiritual Quotient and Academic Resilience Of High School Students During The Covid-19 Pandemic - Eryna Mariestha Siahaan; Doddy Hendro Wibowo (Universitas Muhammadiyah Banjarmasin, 2022)
Students should have the ability to deal with challenging and stressful situations. This study aims to determine the correlation between spiritual quotient and academic resilience of high school students during the covid-19 pandemic. This study has 135 subjects from SMA SLAPUR with a simple random sampling technique. The measuring instrument used in this research is the Spiritual Quotient Scale and The Academic Resilience Scale (ARS-30). The results of the analysis using the Pearson Product Moment correlation show the coefficient value of (p<0.05) it’s mean there a significant positive relationship between spiritual quotient and academic resilience of high school students during the covid-19 pandemic. The implication of the research is that students and teachers should cooperate in developing and implementing a program of self-development activities related to spiritual quotient and academic resilience.